Problematic Social Media Use, Self-Objectification, and Body Image Disturbance: The Moderating Roles of Physical Activity and Diet Intensity - Çınaroğlu M; Yılmazer E (Psychology Research and Behavior Management)
Metin Çınaroğlu,1,* Eda Yılmazer2,* 1Psychology Department, İstanbul Nişantaşı University, İstanbul, Türkiye; 2Psychology Department, Beykoz University, İstanbul, Türkiye*These authors contributed equally to this workCorrespondence: Metin Çınaroğlu, İstanbul Nişantaşı University, Maslak Mahallesi, Taşyoncası Sokak, No: 1V ve No: 1Y, Sarıyer-İstanbul, Türkiye, Email metincinaroglu@gmail.comPurpose: This study examines the relationship between problematic social media use, self-objectification, and body image disturbance in women, with physical activity and diet intensity as moderators. It also explores the psychological outcomes of depression and anxiety.Methods: A cross-sectional study was conducted with 594 women aged 18– 65 in Istanbul, Türkiye. Participants completed validated measures assessing social media use, self-objectification, body image disturbance, physical activity, diet intensity, depression, and anxiety. A moderated mediation analysis was performed.Results: Self-objectification significantly mediated the relationship between problematic social media use and body image disturbance (b = 0.14, SE = 0.03, 95% CI [0.10, 0.21], p < 0.01, R² = 0.18). Physical activity buffered this effect (b = − 0.12, SE = 0.05, p = 0.02, d = 0.36), while diet intensity exacerbated it (b = 0.15, SE = 0.04, p < 0.01, d = 0.42). Body image disturbance also mediated the association between social media use and depression (b = 0.18, SE = 0.05, p < 0.01, R² = 0.22) and anxiety (b = 0.16, SE = 0.04, p < 0.01, R² = 0.19).Conclusion: The findings highlight the dual roles of physical activity and diet intensity in shaping body image outcomes. The study underscores the need for targeted interventions to mitigate the negative impact of social media-driven self-objectification on body image and mental health.Plain Language Summary: This study examines how social media use affects women’s body image and mental health, focusing on the unique cultural environment of Istanbul, Türkiye. Social media platforms, particularly those emphasizing visuals, often promote unrealistic beauty standards. These images can lead women to internalize these ideals, evaluating themselves based on appearance rather than personal qualities. This process, known as self-objectification, may result in dissatisfaction with their own bodies and contribute to mental health challenges such as depression and anxiety.We surveyed 594 women aged 18– 65, analyzing their social media habits, body image concerns, physical activity levels, dieting behaviors, and mental health symptoms. We found that social media use is linked to greater body dissatisfaction through self-objectification. However, the extent of this relationship depends on lifestyle factors. Women who engaged in regular physical activity experienced less impact from self-objectification on their body image, suggesting that exercise can protect against harmful effects. On the other hand, restrictive dieting intensified these effects, highlighting the risks associated with extreme dieting practices.Our findings also show that body dissatisfaction can lead to broader mental health challenges, including increased symptoms of depression and anxiety. These results emphasize the need for targeted interventions to promote healthier social media habits, balanced physical activity, and mindful eating practices. By addressing these factors, we can support women in navigating the pressures of social media and cultural beauty standards, fostering better mental health and body image.Keywords: social media use, self-objectification, body image disturbance, physical activity, diet intensity